Integrated Pest Management at Home Series: Does your head itch? Facts About Head Lice - Nelly Nelson; LuAnn Duncan; Jenny Rodriguez; Katherine Allen; Karen Stauderman; Lisa Hamilton; Faith Oi (EDIS)
My head is itchy... could I have head lice? What are head lice? How do people get them? How do people inspect for them? How can people treat head lice? What should schools do about head lice? Will pesticides work? Will home remedies work? What can happen?!